ANALISIS PENETAPAN KADAR NIPAGIN DALAM SEDIAAN BODY LOTION TIE (TANPA IZIN EDAR) YANG BEREDAR DI PASAR TRADISIONAL KOTA PALU - Vini Mandasari; Syariful Anam; Yonelian Yuyun (KOVALEN: Jurnal Riset Kimia, 2016)
This study aims to determine the levels of nipagin as preservative in body lotions which have no marketing authorization (MA). Each sample was taken from 4 traditional markets located in Palu City. The assay of nipagin in the body lotions was done by using ultraviolet (UV) at wavelength of 257 nm. From 8 different samples, 5 of them contain nipagin of which levels are as follows: A1 = 0.232%; A2 = 0.229%; B1 = 0.124%; B2 = 0.120%; C1 = 0.120%; C2 = 0.117%; and D1 = 0.267%; D2 = 0.273%; and F1 = 0.213%; and F2 = 0.215%. Based on the results obtained, those body lotions that have no marketing authorization meet the requirement of nipagin’s preservative levels according to Analitical Method of National Center for Drug and Food Testing, in which the allowed levels of nipagin for body lotion is 0.4%.Keywords: Body Lotion, Nipagin, Ultraviolet Spectrophotometer.